H HUBUNGAN PENDERITA DIABETES MILITUS TERHADAP TINGKAT KEPARAHAN GAGAL GINJAL KRONIK PADA PASIEN YANG MENJALANI HEMODIALISIS DI RS BANJARMASIN - harun, lukman; Nurhikmah, Nurhikmah; Riyadi, Machli (LPPM Universitas Sari Mulia, 2023)
Background : Efforts to achieve the vision and mission of a healthy Indonesia in 2025 are still experiencing problems due to the high number of degenerative diseases including chronic kidney failure. According to WHO 2018, kidney failure is a chronic disease with the 20th highest mortality rate in the world. In Indonesia in 2018 there were 713,783 people suffering from kidney failure. Meanwhile, the most risk factors are due to diabetes mellitus 33.3% in Banjarmasin Objective: This study was to determine the relationship between diabetes mellitus sufferers and the severity of chronic kidney failure in patients undergoing hemodialysis. Method: This type of research is quantitative with an analytical research design with a cross sectional approach. Done at one time using documentation sheets to collect data on respondents with a population of 567 respondents and a sample of 216 respondents, using purposive sampling technique, with chi-square analysis. Result: From this study, the results of univariate analysis of diabetes mellitus 34 (15.7%), 182 diabetes mellitus (84.3%) did not, End Renal Diseases 151 (70%), Non End Renal 65 (30%). The results of bivariate analysis using chy-square analysis with a P-value of 0.011 <0.05 there is a significant relationship between diabetes mellitus and the severity of kidney failure Conclusion: there is a significant relationship between diabetes mellitus and the severity of kidney failure